Employment trends in the U.S. Electricity Sector, 2008–2012. (July 2015) - Haerer, Drew; Pratson, Lincoln
Abstract: Between 2008–2012, electricity generated (GWh) from coal, the longtime dominant fuel for electric power in the US, declined 24%, while electricity generated from natural gas, wind and solar grew by 39%, 154%, and 400%, respectively. These shifts had major effects on domestic employment in those sectors of the coal, natural gas, wind and solar industries involved in operations and maintenance (O&M) activities for electricity generation. Using an economic input–output model, we estimate that the coal industry lost more than 49, 000 jobs (12%) nationally over the five-year period, while in the natural gas, solar, and wind industries, employment increased by nearly 175, 000 jobs (21%). We also combine published ratios for jobs per unit of fuel production and per megawatt of power plant capacity with site-specific data on fuel production and power plant retirements, additions and capacity changes to estimate and map direct job changes at the county level. The maps show that job increases in the natural gas, solar and wind industries generally did not occur where there were significant job losses in the coal industry, particularly in West Virginia and Kentucky. Highlights: We examine shifts in the U.S. electricity industry from 2008–2012 by sector. We use an economic input–output model to estimate direct and indirect jobs. We conducted an analytical, county level geospatial analysis using ArcGIS. The coal sector suffered significant job losses, mainly in traditional coal regions. Those losses were offset by gains, but typically not in the same geographic areas.